High frequency of OTOF mutations in Chinese infants with congenital auditory neuropathy spectrum disorder. Issue 3 (11th March 2016) - Zhang, Q.‐J.; Han, B.; Lan, L.; Zong, L.; Shi, W.; Wang, H.‐Y.; Xie, L.‐Y.; Wang, H.; Zhao, C.; Zhang, C.; Yin, Z.‐F.; Wang, D.‐Y.; et al.
Abstract : Auditory neuropathy spectrum disorder (ANSD) is one of the most common diseases leading to hearing and speech communication barriers in infants and young children. The OTOF gene is the first gene identified for autosomal recessive non‐syndromic ANSD, and patients with OTOF mutations have shown marked improvement of auditory functions from the cochlear implantation, but the true involvement of OTOF mutations in Chinese ANSD patients is still unknown which precludes the effective management of this disease. Here, we investigated the contribution of OTOF mutations to congenital ANSD patients in China. In all, 37 infants and young Children with ANSD were screened for all the exons of OTOF gene, of them 34 patients had no neonatal risk factors who were considered as congenital ANSD. The clinical manifestation and audiometric features were also investigated and compared in patients with and without OTOF mutations. In all, 14 of these subjects were shown to carry two or three mutant alleles of OTOF with the high frequency of 41.2% in congenital ANSD patients. In total, 15 novel pathogenic mutations and 10 reported mutations were identified. Our results confirmed that mutations in OTOF gene were a major cause of congenital ANSD in China. Identification of OTOF mutations can facilitate diagnosis, clinical intervention and counseling for congenital ANSD. Abstract :